The Limbic System Conception and Its Historical Evolution - Marcelo R. Roxo; Paulo R. Franceschini; Carlos Zubaran; Fabrício D. Kleber; Josemir W. Sander (The Scientific World Journal)
Throughout the centuries, scientific observers have endeavoured to extend their knowledge of the interrelationships between the brain and its regulatory control of human emotions and behaviour. Since the time of physicians such as Aristotle and Galen and the more recent observations of clinicians and neuropathologists such as Broca, Papez, and McLean, the field of affective neuroscience has matured to become the province of neuroscientists, neuropsychologists, neurologists, and psychiatrists. It is accepted that the prefrontal cortex, amygdala, anterior cingulate cortex, hippocampus, and insula participate in the majority of emotional processes. New imaging technologies and molecular biology discoveries are expanding further the frontiers of knowledge in this arena. The advancements of knowledge on the interplay between the human brain and emotions came about as the legacy of the pioneers mentioned in this field. The aim of this paper is to describe the historical evolution of the scientific understanding of interconnections between the human brain, behaviour, and emotions.